Defence‐related pathways, phytohormones and primary metabolism are key players in kiwifruit plant tolerance to Pseudomonas syringae pv. actinidiae - Nunes da Silva, Marta; Carvalho, Susana M. P.; Rodrigues, Ana M.; Gómez‐Cadenas, ‪Aurelio; António, Carla; Vasconcelos, Marta W. (Plant, cell and environment, 2022)
The reasons underlying the differential tolerance of Actinidia spp. to the pandemic pathogen Pseudomonas syringae pv. actinidiae (Psa) have not yet been elucidated. We hypothesized that differential plant‐defence strategies linked to transcriptome regulation, phytohormones and primary metabolism might be key and that Actinidia chinensis susceptibility results from an inefficient activation of defensive mechanisms and metabolic impairments shortly following infection. Here, 48 h postinoculation bacterial density was 10‐fold higher in A. chinensis var. deliciosa than in Actinidia arguta, accompanied by significant increases in glutamine, ornithine, jasmonic acid (JA) and salicylic acid (SA) (up to 3.2‐fold). Actinidia arguta showed decreased abscisic acid (ABA) (0.7‐fold), no changes in primary metabolites, and 20 defence‐related genes that were only differentially expressed in this species. These include GLOX1, FOX1, SN2 and RBOHA, which may contribute to its higher tolerance. Results suggest that A. chinensis' higher susceptibility to Psa is due to an inefficient activation of plant defences, with the involvement of ABA, JA and SA, leading to impairments in primary metabolism, particularly the ammonia assimilation cycle. A schematic overview on the interaction between Psa and genotypes with distinct tolerance is provided, highlighting the key transcriptomic and metabolomic aspects contributing to the different plant phenotypes after infection. Summary Statement The pandemic bacterium P. syringae pv. actinidiae is currently the most important pathogen affecting kiwifruit productivity worldwide. Given the absence of sustainable and effective mitigation strategies, it is imperative to understand plant tolerance mechanisms that could support crop improvement and better agronomical practices. Here, we found that plant susceptibility to Psa results from an inefficient activation of plant defences, involving the jasmonic acid and salicylic acid pathways, and leads to impairments in primary metabolism, particularly the ammonia assimilation cycle. Tolerance is most likely due to a more strategic defensive and metabolic readjustment, resulting from the activation of specific defence‐related genes and to the downregulation of the abscisic acid pathway.